Analysis of volatile components of Tilapia enzymolysis solution after different deodorization treatments. Issue 1 (November 2020) - Li, Yahui; Zhou, Wei; Cao, Yupo; Gong, Xiao; Li, Jihua; Lu, Xuli; Dai, Yaping
Abstract: The fishy smell value was used as the detection index, and the three methods of yeast fermentation, activated carbon adsorption, and β-CD embedding were used to deodorize. The results showed that the yeast fermentation had a good deodorization effect on the tilapia enzymolysis solution(TES). The volatile components of TES after deodorization were analyzed by GC-MS, and the results showed that the smelly substances of the TES were mainly aldehydes and alcohols. The main smelly substances of TES are aldehydes and alcohols, and the main volatile compounds are heptanal, 2-heptanal, benzaldehyde, octanal, 2-octenal, (E)-nonanal, 2-oecenal, (Z)-, 2, 4-nonadienal, heptanol, 1-Octen-3-ol, Octenol <2-trans-> etc.